The Praetorian Trap: the Problems and Prospects of Military Disengagement - Dare, L. O. (Obafemi Awolowo University Press, 2013)
Nigeria has spent 19 of her 29 years of political independence under military rule, and military rule as far as the quality of life of the ordinary citizen goes, has not been a success story. Since 19 years of military rule has ended in this undesirable situation, the logic of the argument goes further; if we end both present military rule and future military intervention, we may soon be on the way to establishing a more desirable future. In short, there seems an agreement that military rule is bad. It is not only the "Ivory Tower extremists" who share this view. It is equally pervasive among the military. It is in realization of this that I, with deep humility present in this lecture a synthesis of my views on one of the perennial issues of our time, the problems and prospects of military disengagement.